Quality of life of hemodialyzed patients with the consideration of the type of vascular access - Michalik, Anna; Maciejczyk, Natalia; Skoczylas, Kornelia (Journal of Education, Health and Sport, 2025)
Introduction: Kidney disease is a major challenge for modern medicine, despite advances in its diagnosis and therapy. Hemodialysis, as one of the key renal replacement therapies, sustains patients' vital functions, but is associated with significant challenges in terms of the quality of life. Aim: To assess the quality of life of patients undergoing hemodialysis with consideration of the type of vascular access. Material and method: The study was conducted from November 2023 to March 2024 among patients of dialysis stations in the district of Jastrzębie, diversified in terms of age, place of residence, education, and marital status. The study used a diagnostic survey method with a self-constructed questionnaire and a KDQOL-SFTM tool. Results and conclusions: Patients with a fistula tend to have a higher quality of life, better physical and social functioning, and better overall health than patients using a vascular catheter. Gender and place of residence have no significant effect on the quality of life of hemodialyzed patients, regardless of the type of vascular access. Patients under 60 years of age show better physical health than older patients. Secondary and higher education correlates with higher quality of life in terms of symptoms. Marital status has a significant impact on physical health. Shorter duration of dialysis treatment is associated with better quality of life in terms of symptoms, disease quality of life and mental health. The absence of dialysis complications correlates with higher quality of life in terms of symptoms, quality of life in disease and physical health. The results of the study highlight the importance of the type of vascular access and socio-demographic factors in assessing the quality of life of hemodialyzed patients.